Preliminary Memorandum on the Fourth Five Year Plan of Assam - Government of Assam (Government of Assam, 1965)
The Fourth Five-Year Plan of Assam (1966–71) outlines a comprehensive strategy for socio-economic development, aiming to achieve sustainable growth while addressing the state’s unique challenges. The plan emphasizes agricultural self-sufficiency with a 5% annual growth target, industrial expansion, and power generation to support economic and regional energy needs. Key initiatives include flood control, road and bridge development, and mineral resource exploitation. Investments in education, vocational training, social welfare, and backward area development aim to improve human capital and living standards. The plan integrates local governance, community participation, and strategic resource mobilization to foster holistic, sustainable development in Assam.
Government of Assam Planning and Development Department (January 1965)
Government of Assam Planning and Development Department (January 1965)
Keywords: Assam; State Plan; Agriculture; Industrial Development; Power Generation; Flood Control; Infrastructure; Employment; Mineral Development; Education; Social Welfare; Transport